Nucleolar-nucleoplasmic shuttling of TARG1 and its control by DNA damage-induced poly-ADP-ribosylation and by nucleolar transcription - Mareike Bütepage (Nature Portfolio, 2018)
Abstract Macrodomains are conserved protein folds associated with ADP-ribose binding and turnover. ADP-ribosylation is a posttranslational modification catalyzed primarily by ARTD (aka PARP) enzymes in cells. ARTDs transfer either single or multiple ADP-ribose units to substrates, resulting in mono- or poly-ADP-ribosylation. TARG1/C6orf130 is a macrodomain protein that hydrolyzes mono-ADP-ribosylation and interacts with poly-ADP-ribose chains. Interactome analyses revealed that TARG1 binds strongly to ribosomes and proteins associated with rRNA processing and ribosomal assembly factors. TARG1 localized to transcriptionally active nucleoli, which occurred independently of ADP-ribose binding. TARG1 shuttled continuously between nucleoli and nucleoplasm. In response to DNA damage, which activates ARTD1/2 (PARP1/2) and promotes synthesis of poly-ADP-ribose chains, TARG1 re-localized to the nucleoplasm. This was dependent on the ability of TARG1 to bind to poly-ADP-ribose. These findings are consistent with the observed ability of TARG1 to competitively interact with RNA and PAR chains. We propose a nucleolar role of TARG1 in ribosome assembly or quality control that is stalled when TARG1 is re-located to sites of DNA damage.